Peace Education in History Learning at MAN Medan - Muhammad Ricky Hardiyansyah; Aditya Darma; Muhammad Adika Nugraha (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to reveal how peace education is conveyed through history learning at MAN Medan. The research method used in this research is a qualitative research method with a case study approach. The main informants in this study were history teachers and students at MAN 2 Model Medan and MAN 1 Medan. The results of the study show that peace education has a correlation with history education, one of which is with material on conflict and peace in history lessons. Peace education through history education is useful for conveying the values of peace, and can be conveyed effectively in history lessons. In addition, several things that become obstacles in conveying affective values in history learning are also obstacles to the implementation of peace education in history learning.